Understanding the impact of within-field Olsen P variation on common wheat production in Olsen P deficient soils - Marco Mancini; Lorenzo Guerrini; Carolina Fabbri; Simone Orlandini; Marco Napoli (Journal of Agriculture and Food Research, 2024)
This study investigates the influence of Olsen phosphorus (Ps) within-field variability on common wheat production in Ps-deficient soil. It covers a comprehensive investigation conducted over two growing seasons in Tuscany, Italy, aiming to evaluate the impact of within-field Ps variation on common wheat production and crop responses to different agronomic treatments. Field experiments were undertaken, employing 24 treatments, including 4 wheat varieties, 2 seeding densities, and 3 nitrogen fertilization levels. Soil samples were collected to determine within field variability of main soil properties. At harvesting, aboveground biomass was collected to determine grain yield, straw, and total protein content. Firstly, an ANOVA was performed to account for the effect of the agronomical treatments on crop parameters, namely the Agronomical Input Model (AIM). Then, soil total nitrogen (Ns) and Ps, were added as covariates in a new model, namely the Agronomical and Soil Input Model (ASIM). Results showed a significant spatial variability of Ps within the fields, ranging between 13.7 and 17.4 mg kg-1. Despite this minimal variation in Ps, we observed a linear increase in GY of about 1430 kg ha-1 for each increase of 1 mg kg-1 in Ps. Further studies should be conducted to account for non-linear responses at both lower and higher Ps levels. The ASIM model outperformed AIM, indicating a notable increase in predictive accuracy for both grain yield and protein concentration due to its incorporation of soil parameters. The variance explained by ASIM in predicting the grain yield and protein concentration in grain increased by about 11.0 % and 17.3 %, respectively, with respect to AIM. The study emphasizes the necessity of managing within-field Ps variability through targeted fertilization strategies to enhance wheat production in Ps-deficient soils. By addressing soil nutrient variability, this research aims to contribute to more precise and efficient common wheat production systems.